Detection of VP6 gene of Rotavirus in Feces of Diarrhoeic calves, kids, lambs, piglets, pups and human infants by Reverse Transcriptase–Polymerase Chain Reaction - Tumlam, U.M.; Ingle, V.C.; Tembhurne, P.A.; Kurkure, N.V.; Chaudhari, S.P.; Chitambar , S.D.; Bhoyar , S. (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The present study was undertaken on VP6 gene based detection of Rotavirus in faeces of diarrheic bovine, porcine, caprine, ovine, canine species of animals and human. A total of 44faecal samples from bovine calves, piglets, kids, lambs, pups and human infants (0-1 yr of age) were screened for the detection of group A Rotavirus by VP6 gene based RT–PCR assay. Out of 44 samples total of 43 (97.72%) samples were found positive for Rotavirus. Samples from all other species were found cent percent positive for group A Rotavirus except for the human infants where 17 out of 18 samples were found positive. VP6 gene base RT-PCR study confirmed the prevalence of group A Rotavirus in animals and human species. RT–PCR assay can be used as a sensitive and specific assay for the rapid detection of group A Rotavirus in faecal samples.
Keywords: Group A Rotavirus; VP6 gene; diarrhoea; RT–PCR